2021
DOI: 10.1002/er.6595
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional materials and synthesis, energy storage, utilization, and conversion applications of two‐dimensional MXene materials

Abstract: Summary Owing to the first‐rate residences of graphene, the research had been achieved on novel two‐dimensional (2D) materials. The MXene is a 2D inorganic compound that consists of transition metal carbides, nitrides, and carbonitrides. Ti₃C₂, the primary 2D‐layered MXene, was reported in 2011. This material that is a layered bulk material analogous to graphite, changed into derived from its 3D phase, is Ti₃AlC₂ MAX. The start of this review through reviewing the structures and morphologies and their fabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 147 publications
0
7
0
Order By: Relevance
“…The heterostructures of 2D materials were also studied for the application of photodetectors. The common example is graphene and MoS 2 heterostructures applied for the photodetector application, and results concluded that the photo gains were more than 10. , …”
Section: Promise Of 2d Materials To Address the Limitations Of The Co...mentioning
confidence: 99%
See 2 more Smart Citations
“…The heterostructures of 2D materials were also studied for the application of photodetectors. The common example is graphene and MoS 2 heterostructures applied for the photodetector application, and results concluded that the photo gains were more than 10. , …”
Section: Promise Of 2d Materials To Address the Limitations Of The Co...mentioning
confidence: 99%
“…The common example is graphene and MoS 2 heterostructures applied for the photodetector application, and results concluded that the photo gains were more than 10. 8,146 Short Overview on Synthesis of Heterostructures. There are two main conventional methods to synthesize or construct the 2D-materialbased heterostructures: one is mechanical assembly, and the other is the in situ growth method.…”
Section: Electrochemical Characteristics Of Borophene-based Batterymentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional materials have large surface-to-volume ratios and good dispersion in liquid media, giving unique functions. Their applications in separation, 46 electronic engineering, 47 energy and gas storage, 48 light capture and conversion 49 have aroused great interest. Two-dimensional supramolecular organic luminescent assemblies include single-layer metal–organic framework (MOF), 50 covalent organic framework (COF), 51 supramolecular organic framework (SOF), 52 and 2D polyrotaxane.…”
Section: Two- Dimensional (2d) Supramolecular Organic Luminescent Ass...mentioning
confidence: 99%
“…Compared to the top-down approach, the bottom-up approach offers several advantages, including higher atomic utilization, better control of morphology, and a narrower size distribution [17,18]. The synthesis of TMD QDs using the bottom-up approach has already been described in unmerous reports and does not need to be repeated here [9,[17][18][19][20][21]. In the top-down approach, bulk materials are decomposed and converted into QDs through physical, chemical, or electrochemical methods.…”
Section: Bottom-up and Top-down Approachesmentioning
confidence: 99%